LINGUISTIC ASPECT OF ENGLISH AND UZBEK COMPOUND WORDS - Ashirova Madina To’rayevna (Western European Studies, 2024)
Culture and language are intricately intertwined and reciprocally influential. Furthermore, serving as a crucial element of language, compound words function as a "portal" through which one can examine the national and cultural traits of a particular country. This study aims to analyze the distinctive national characteristics—whose origins are also explored—by comparing and contrasting compound words in Uzbekistan and English in terms of their national values and cultural significances. By enhancing comprehension of the disparities between Uzbek and English cultures and how compound words mirror national values, it is anticipated that this discourse will enhance appreciation for compound words and their usage, while also promoting more meaningful cross-cultural interactions between the two linguistic communities
Keywords: compound words; national values; language